Toxicological studies of some microbial compounds and their mixtures against 2nd instar larvae of cotton leafworm spodoptera littoralis (Boisd) - Anwar, E.M. (2007)
The effect of various microbial pesticides and its binary mixtures against 2nd instar larvae of collon leafworm Spooopfera littoralis (Boisd)
Includes reference.
Summary in Arabic.
1
Keywords: Cotton -- leafworm; Spodoptera littoralis -- Control; Pesticides -- Toxicologie; Insecticide resistance; Mixtures